Towards global consensus on core outcomes for hidradenitis suppurativa research: an update from the HISTORIC consensus meetings I and II. (1st March 2018) - Thorlacius, L.; Garg, A.; Ingram, J.R.; Villumsen, B.; Theut Riis, P.; Gottlieb, A.B.; Merola, J.F.; Dellavalle, R.; Ardon, C.; Baba, R.; Bechara, F.G.; Cohen, A.D.; et al.
Summary: Background: A core outcomes set (COS) is an agreed minimum set of outcomes that should be measured and reported in all clinical trials for a specific condition. Hidradenitis suppurativa (HS) has no agreed‐upon COS. A central aspect in the COS development process is to identify a set of candidate outcome domains from a long list of items. Our long list had been developed from patient interviews, a systematic review of the literature and a healthcare professional survey, and initial votes had been cast in two e‐Delphi surveys. In this manuscript, we describe two in‐person consensus meetings of Delphi participants designed to ensure an inclusive approach to generation of domains from related items. Objectives: To consider which items from a long list of candidate items to exclude and which to cluster into outcome domains. Methods: The study used an international and multistakeholder approach, involving patients, dermatologists, surgeons, the pharmaceutical industry and medical regulators. The study format was a combination of formal presentations, small group work based on nominal group theory and a subsequent online confirmation survey. Results: Forty‐one individuals from 13 countries and four continents participated. Nine items were excluded and there was consensus to propose seven domains: disease course, physical signs, HS‐specific quality of life, satisfaction, symptoms, pain and global assessments. Conclusions: The HISTORIC consensus meetings I and II will be followed by further e‐Delphi rounds to finalize the core domain set, building on the work of the in‐person consensus meetings.